Extension Theorem for Complex Clifford Algebras-Valued Functions on Fractal Domains. (30th March 2010) - Abreu-Blaya Abreu-Blaya, Ricardo Ricardo; Bory-Reyes Bory-Reyes, Juan Juan; Bosch Bosch, Paul Paul
Abstract : Monogenic extension theorem of complex Clifford algebras-valued functions over a bounded domain with fractal boundary is obtained. The paper is dealing with the class of Hölder continuous functions. Applications to holomorphic functions theory of several complex variables as well as to that of the so-called biregular functions will be deduced directly from the isotonic approach.